2007
DOI: 10.1007/s10549-007-9613-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of mitochondrial DNA 4977-bp deletion in sporadic breast cancer and benign breast diseases

Abstract: The mitochondrial DNA (mtDNA) 4977-bp deletion ( mtDNA 4977 mutation) is one of the most frequently observed mtDNA mutations in human tissues, and may play a role in carcinogenesis. Only a few studies have evaluated mtDNA 4977 mutation in breast cancer tissue, and the findings have been inconsistent, which may be due to methodological differences. In this study, we developed a quantitative real-time PCR assay to assess the level of the mtDNA 4977 mutation in tumor tissue samples from 55 primary breast cancer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 33 publications
2
39
0
Order By: Relevance
“…In case of human oocytes it has been confirmed that age exhibits the only significant correlation with the presence of the 4977 bp deletion, while other parameters like smoking or early follicular phase FSH did not reveal any correlation (Chan et al, 2005). In recent years, a number of carefully conducted studies reported, that the level of the 4977 bp deletion is not increased in different tumour tissues (Dani et al, 2004;Dai et al, 2006;Ye et al, 2007) and in conditions associated with chronic inflammation like ulcerative colitis (Fukushima and Fiocchi, 2004). Though our data display a great variability even in individuals of the same age group, the large pool of data may help to discriminate between physiological ageing and pathological conditions associated with accelerated ageing.…”
Section: Discussionmentioning
confidence: 97%
“…In case of human oocytes it has been confirmed that age exhibits the only significant correlation with the presence of the 4977 bp deletion, while other parameters like smoking or early follicular phase FSH did not reveal any correlation (Chan et al, 2005). In recent years, a number of carefully conducted studies reported, that the level of the 4977 bp deletion is not increased in different tumour tissues (Dani et al, 2004;Dai et al, 2006;Ye et al, 2007) and in conditions associated with chronic inflammation like ulcerative colitis (Fukushima and Fiocchi, 2004). Though our data display a great variability even in individuals of the same age group, the large pool of data may help to discriminate between physiological ageing and pathological conditions associated with accelerated ageing.…”
Section: Discussionmentioning
confidence: 97%
“…However, the pathogenesis of mtDNA decrease in cancers remains unclear. It was hypothesised that mitochondrial respiratory dysfunction and damage of mtDNA, such as mutation, deletion or depletion, in carcinogenesis may course the quantitative alterations (Ye et al 2008). Those alterations of mtDNA could correlate with increased risk (Mosquera-Miguel et al 2008;Bai et al 2007) and increased invasiveness of cancer (Simonnet et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The common mtDNA 4,977-bp deletion has been shown to accumulate with age, primarily in postmitotic tissues (13) and cancers (20)(21)(22)(23)(24). The different accumulation rate could result from genetic factors (such as tissue type), energy demand, intracellular oxidative stress levels, environmental insults, or cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is increased by environmental insults, such as UV irradiation (15)(16)(17), cigarette smoking (18,19) and betel quid chewing (20). Moreover, the mtDNA 4,977-bp deletion is also frequently detected in various types of cancer tissues (20)(21)(22)(23)(24). Due to its good correlation with oxidative damage levels in somatic tissues, we hypothesized that the mtDNA deletion would be more frequently detected in breast tissues of the patients with NQO1 609 C/T or T/T genotype than those with C/C genotype.…”
Section: Introductionmentioning
confidence: 99%